Review of Active Fire Protection Compliance Based on National Fire Protection Association (NFPA) Standards in Building X, PT Y - Nita, Widian; Cut Alia Keumala Muda; Fierdania Yusvita; Namira Wadjir Sangadji; Muhammad Rizky Jayana (LPPM Universitas Mohammad Husni Thamrin, 2026)
Fire remains a global problem with a significant impact on life safety and economic losses. Data from the National Fire Protection Association shows that in 2023, there were approximately 1,389,000 fires in the United States, including 470,000 building fires, resulting in fatalities and billions of dollars in losses. Office buildings have a high fire risk due to the intensity of activity and the use of electrical installations, requiring fire protection systems that adhere to National Fire Protection Association (NFPA) standards. In 2025, a fire occurred on the first floor of Building X, South Jakarta, triggered by a short circuit due to an air conditioning drainage leak and unprotected cables. This study aimed to assess the compliance of fire extinguishers (APAR), hydrants, sprinklers, detectors, and fire alarms with NFPA standards. The method used was qualitative with a narrative design through observation using the NFPA checklist, measuring installation distances, documenting equipment, and reviewing documents, which were then analyzed chronologically (restorying). The results showed that 35.7% of fire extinguishers did not comply with NFPA 10, 13.3% of fire hydrants did not comply with NFPA 14, and 25% of sprinklers did not comply with NFPA 13. All detectors and alarms were 100% compliant with NFPA 72. Installation improvements, increased maintenance, and regular monitoring in accordance with NFPA standards are recommended to minimize fire risk.